Retrograde mesenteric perfusion from the deep femoral artery in a patient with a recurrent anastomotic aneurysm in the groin: a case report - Geng, Benoit; Menth, Markus; Widmer, Lucien; Egger, Bernhard; Psathas, Emmanouil (Frontiers in Surgery, 2023)
In patients with atherosclerotic disease in two of the three main vessels in the splanchnic circulation, symptoms of chronic mesenteric ischemia may arise, depending on the disease chronicity and the presence of mesenteric collateral pathways. The most commonly described collateral pathways are between the celiac artery (CA), superior mesenteric artery (SMA), and inferior mesenteric artery (IMA); and between the IMA and the internal iliac artery (IIA). Another collateral network between the deep femoral artery and the IIA can also become important, especially in patients with aorto-iliac occlusion. Here we report a patient with a symptomatic anastomotic aneurysm of the right femoral artery after a previous aorto-bi-femoral bypass. This patient’s bowel viability relied on a well-developed collateral network from the ipsilateral deep femoral artery. This unusual anatomy required special surgical considerations and planning, to minimize the risk of perioperative mesenteric ischemia. During open repair, distal femoral debranching with a distal-to-proximal anastomotic sequence allowed minimizing of the ischemic time, and avoidance of potential ischemic complications from the visceral circulation. This case emphasizes the importance and benefit of the deep femoral artery and its collaterals as a reserve network of the splanchnic circulation. Favorable outcomes can be achieved with careful analysis of the preoperative imaging and proper planning, with adaptation of the surgical strategy.